The Negative Effect of Ability-Focused Praise on the “Praiser’s” Intrinsic Motivation: Face-to-Face Interaction - Kakinuma, Kyosuke; Nishiguti, Fumika; Sonoda, Kotoe; Tajiri, Haruhi; Tanaka, Ayumi (Frontiers in Psychology, 2020)
Most previous research has demonstrated that receiving ability-focused praise (e.g., “You are smart”) negatively affects intrinsic motivation following failure. Surprisingly, a recent study showed that ability-focused praise affects not only the praisee but also the person offering praise, that is, the praiser. However, evidence of the effects on the praiser is quite limited, despite the utility of praise in education. Therefore, the present study employed face-to-face interaction to advance the knowledge of the effects of praise on the praiser. Two experiments were conducted in which undergraduate participants (n = 39 and n = 51) praised a research confederate. We measured attentional engagement using an eye-tracker as a behavioral indicator of intrinsic motivation, as well as self-reported task enjoyment. To estimate the effect of praise, we combined the results of two experiments and conducted a Bayes factor meta-analysis. The results showed that in the ability praise group, participants’ attentional engagement in a task was significantly lower than in the control group. The present finding indicates that ability-focused praise negatively affects the praiser’s intrinsic motivation and suggests that praise should be used with caution in social and educational contexts.